Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1039/d2lc00406b
|View full text |Cite
|
Sign up to set email alerts
|

An integrated magneto-opto-fluidic biosensor for rapid on-chip assay of respiratory viruses of livestock

Abstract: This work demonstrated an on-chip virus analysis technology that can characterize multiple viruses in clinical samples with automated sample processing and detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For virus detection by PCR, which typically involves samples extraction, nucleic acid purification, and detection, Zhang Q. et al (2022) developed an immunomagnetic virus enrichment method using MNPs and a biosensor system-on-chip (IMOF) based on photonic crystals (PC) ( Figure 4 ). This approach employed antibody-functionalized MNPs to specifically target and concentrate the virus while improving the output efficiency of the PC sensor, enabling automated detection.…”
Section: The Impact Of Magnetic Nanoparticles On Biological Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For virus detection by PCR, which typically involves samples extraction, nucleic acid purification, and detection, Zhang Q. et al (2022) developed an immunomagnetic virus enrichment method using MNPs and a biosensor system-on-chip (IMOF) based on photonic crystals (PC) ( Figure 4 ). This approach employed antibody-functionalized MNPs to specifically target and concentrate the virus while improving the output efficiency of the PC sensor, enabling automated detection.…”
Section: The Impact Of Magnetic Nanoparticles On Biological Detectionmentioning
confidence: 99%
“…(C) Diagram illustrating the label-free analysis via resonant reflection spectra measured from PC sensors, with MNPs enhancing the shift of the resonant wavelength due to the absorption of target MNP–virus conjugates. Reprinted with permission from Zhang Q. et al (2022) .…”
Section: The Impact Of Magnetic Nanoparticles On Biological Detectionmentioning
confidence: 99%
“…The purification of samples is also effective [103,194]. The purification often requires large equipment such as centrifuges, but there have been vigorous attempts to integrate a purification unit onto the biosensor chip [195][196][197]. In contrast to passive methods to prevent nonspecific adsorption from occurring as described above, methods to actively remove nonspecifically adsorbed molecules have also been proposed.…”
Section: Attempt To Rationally Extract Signals From Samples With Comp...mentioning
confidence: 99%
“…The design flexibility and development of novel materials have advanced the 3D printing methods used to manufacture respiratory biosensors for monitoring breathing patterns, respiratory rate, virus detection, and lung function, as illustrated in Figure 12. Wearable biosensors have the capability to collect valuable data and provide crucial insights for the timely detection of respiratory illnesses and the optimization of respiratory remedies [152,[208][209][210][211][212][213][214]. Martins et al demonstrated the fabrication of an immunosensor with fused deposition modeling using a conductive filament of carbon black and polylactic acid (PLA).…”
Section: Respiratory Biosensorsmentioning
confidence: 99%